PERANCANGAN TOOLS BERBASIS PYTHON UNTUK MEMANTAU KEAKTIFAN SERVER - Husni Thamrin (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2011)
Information system reliability can be measured by the availability of system when the information is needed. Server activeness is among the important factors to get reliable information system. Inactiveness of servers obstructs information availability and needs an early detection so that system administrator may quickly overcome the problem and restore the system. A tools is needed to help a system admin detect server inactiveness, which alerts the admin of any possible problem. In this research, a tool is created using python programming language to periodically detect activeness of servers simultaneously. The result is logged into a file for later analysis. Whenever the tool detect inactiveness, it sends an email to the admin account and/or send a text message to a specified number. Observation proves that the tools works as expected. The tools should be installed in one of the servers or in a computer close the server farm because network connectivity and computer location have a great influence to the monitoring activity.